REVIEW: Disinformation and the end of democracy? - David Robie (Pacific Journalism Review, 2023)
How to Stand up to a Dictator: The Fight for our Future, By Maria Ressa. London: Penguin Random House, 2022. 301 pages. ISBN 978073559208.